Hölderlin’s mythopoetics in the poem “Like on a holiday…” - Fernandes, João Evangelista (Sofia, 2024)
The article begins with a review of two dissertations that Hölderlin defended in Tübingen, in 1790, in which it will be pointed out how the poet conceives poetry as closely related to myth, which can be considered the basis of his late mythopoetics. In a second moment, some fragments, letters and poems from the period of Iena and Frankfurt will be analyzed, in order to present Hölderlin’s aesthetic-philosophical period, fundamental to understanding the mythopoetic elaborations of the mature period, shortly after the inconclusive tragedy of The Death of Empedocles and his involvement with the theory of tragedy. Finally, there will be an exposition of the Heideggerian interpretation of the poem “Like on a holiday…”, from 1800, in which elements of Hölderlinian mythopoetics will be pointed out highlighted.